Educational interventions to improve outcomes in patients with atrial fibrillation—a systematic review. Issue 11 (7th September 2020) - Palm, Pernille; Qvist, Ina; Rasmussen, Trine Bernholdt; Christensen, Signe Westh; Håkonsen, Sasja Jul; Risom, Signe Stelling
Abstract: Background: Atrial fibrillation (AF) is an emerging epidemic associated with poor mental health and quality of life, as well as morbidity and mortality. Whilst other cardiovascular conditions have demonstrated positive outcomes from educational programmes, this approach is not well integrated in clinical practice in patients with AF. Though evidence in this area is mounting, a thorough overview seems to be lacking. Aim: To assess benefits and harms of educational interventions compared with no intervention in adults with AF. Method: A systematic review and meta‐analysis were performed including the outcomes: Serious adverse events (mortality and readmission), mental health (anxiety and depression), physical capacity, quality of life and self‐reported incidence of symptoms of AF. PubMed, Embase, CINAHL, Cochrane Library and PsycINFO were searched between June and august 2018. Data extraction and quality assessment were performed independently by two reviewers. The Cochrane Risk of Bias tool was applied for the randomised controlled trials and the Amstar Checklist for the systematic reviews. Results: Eight randomised controlled trials and one non‐randomised interventional study were included, with a total of 2388 patients. Comparing with controls patient education was associated with a reduction in: Serious adverse events (Risk Ratio 0.78, CI 95% 0.63‐0.97), anxiety with a mean difference of −0.62 (CI 95% −1.21, −0.04) and depression with a mean difference of −0.74 (CI 95% −1.34, −0.14). Health‐related quality of life and physical capacity was found to increase after patient education, yet, only one study found statistically significant differences between groups. No differences were observed with regards to self‐reported incidence of symptoms of AF. Conclusions: Educational interventions significantly decrease the number of serious adverse events in patients with AF and seem to have a positive impact on mental health and self‐reported quality of life. However, the evidence is limited, and more studies are warranted.